2014
DOI: 10.1136/gutjnl-2014-308252
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of tumour immunity distinguish Asian and non-Asian gastric adenocarcinomas

Abstract: ObjectiveDifferences in gastric cancer (GC) clinical outcomes between patients in Asian and non-Asian countries has been historically attributed to variability in clinical management. However, recent international Phase III trials suggest that even with standardised treatments, GC outcomes differ by geography. Here, we investigated gene expression differences between Asian and non-Asian GCs, and if these molecular differences might influence clinical outcome.DesignWe compared gene expression profiles of 1016 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(162 citation statements)
references
References 50 publications
4
156
1
1
Order By: Relevance
“…22,23 Furthermore, gastric adenocarcinoma in Asian patients is genetically and probably immunologically distinct from Causasian patients. 34 Although these trials showed conflicting results regarding the prognostic impact, all studies described similar frequencies of PD-L1 expression. 22,23 Additionally, we found an increased expression of PD-L1 on metastatic tumor cells further underlining its role in the natural biology of gastric adenocarcinoma.…”
Section: Cd25mentioning
confidence: 99%
“…22,23 Furthermore, gastric adenocarcinoma in Asian patients is genetically and probably immunologically distinct from Causasian patients. 34 Although these trials showed conflicting results regarding the prognostic impact, all studies described similar frequencies of PD-L1 expression. 22,23 Additionally, we found an increased expression of PD-L1 on metastatic tumor cells further underlining its role in the natural biology of gastric adenocarcinoma.…”
Section: Cd25mentioning
confidence: 99%
“…In particular, some studies reported that with the implementation of lymphadenectomy procedures with time, a progressive reduction of locoregional recurrences has been observed (26). However, it should be emphasized that when comparing long-term results from Eastern and Western series, a significant better outcome at the same stage is observed in the former, suggesting potential biological differences related to the tumor, to the ethnicity or to the immunological system (50)(51)(52)(53)(54). When analysing long-term results in Western large series, it is evident that survival rates at advanced pT (serosal involvement) and pN stages (N3a and N3b) are unsatisfactory, even when submitting patients to extended lymphadenectomy (55).…”
Section: Long-term Resultsmentioning
confidence: 91%
“…This is relevant because patients with gastrooesophageal cancer in Asia have, stage for stage, better survival than patients from non-Asian countries and may have a different immune-infiltrate compared with non-Asian patients [16]. Nivolumab has also been evaluated in non-Asian patients in the CheckMate-032 trial which was a non-randomized Phase I/II cohort-study of nivolumab monotherapy and combination nivolumab + ipilimumab (anti-CTLA4) in non-Asian, PD-L1-unselected gastro-oesophageal cancer patients.…”
Section: Nivolumab In Checkmate-032mentioning
confidence: 99%